The Impact of Debate Method on Prospective Elementary Schools’ Communication Ability - Sidiq, Mukti Kanaya; Mustadi, Ali (Universitas Pendidikan Ganesha, 2024)
Social studies education is very important for training communication skills in students up to college, because debate method training is an alternative for forcing students to communicate through pressure (pro-con opinions). This research aims to analyze the relationship between the use of the debate learning model and students' communication skills in MI/SD Basic Social Sciences learning. The type of research used is Quasi Experiment with a Nonequivalent Pretest-Posttest Control Group Design research design. Data collection techniques using questionnaires and documentation. The results of the research are that the average result of the experimental class pretest is in the 0-54 interval, namely 53.53 and is in the very low criteria. Meanwhile, the control class pretest results were in the 0-54 interval, namely 47.30 and were in the very low criteria. The average results of the experimental class post-test were in the 65-79 interval, namely 65.43 and were in the medium criteria, while the control class post-test results were in the 0-54 interval, namely 50.53 and were in the very low criteria. . The probability value for the hypothesis test results, namely (2-tailed) is 0.000. Thus, Ha is accepted, Ho is rejected because 0.000<0.005, so it can be concluded that there is a significant difference in the average score of the communication ability test in the experimental group and the control group.